1997
DOI: 10.1002/(sici)1097-0185(199703)247:3<420::aid-ar14>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Light microscopic quantification of morphological changes during aging in neurons and glia of the rat parietal cortex

Abstract: The stability of neuronal density together with the increased number of glial cells and the changes in neuronal soma size suggest that aged-related cognitive impairment could be a consequence of neuronal dysfunction rather than actual neuronal losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Nonsynaptic mitochondria originate from both neurons and nonneuronal cells. In rat parietal cortex, glial cell density is approximately double the neuronal density, and mitochondria occupy a smaller percentage of the cytosol in glia as compared with neurons (50). Using a similar method to that used in the present study to isolate nonsynaptic mitochondria, Kristian and colleagues (51) found faint peripheral benzodiazepine receptor immunoreactivity, a marker of astrocytic mitochondria (52), in the nonsynaptic mitochondrial fraction in contrast to strong immunoreactivity in mitochondria isolated from cultured astrocytes.…”
Section: Discussionsupporting
confidence: 50%
“…Nonsynaptic mitochondria originate from both neurons and nonneuronal cells. In rat parietal cortex, glial cell density is approximately double the neuronal density, and mitochondria occupy a smaller percentage of the cytosol in glia as compared with neurons (50). Using a similar method to that used in the present study to isolate nonsynaptic mitochondria, Kristian and colleagues (51) found faint peripheral benzodiazepine receptor immunoreactivity, a marker of astrocytic mitochondria (52), in the nonsynaptic mitochondrial fraction in contrast to strong immunoreactivity in mitochondria isolated from cultured astrocytes.…”
Section: Discussionsupporting
confidence: 50%
“…Although data on the ratio between neurons and glia in rat MC is not readily available, parietal and occipital cortices are estimated to have two times more neurons than glial cells on PD10 (Mooney and Napper, 2005). This ratio is decreased significantly by PD115 due to the increase in glial cell number (not a decrease in neuronal counts) with age (Mooney and Napper, 2005; Peinado et al, 1997). …”
Section: Discussionmentioning
confidence: 97%
“…There is conflicting data in the literature as to whether astrocyte number changes with advancing age. For instance, age-related increases in astrocyte number have been documented in the cerebral cortex (Vaughan and Peters, 1974; Peinado et al, 1997; Peinado et al, 1998), the molecular layer of the dentate gyrus (Pilegaard and Ladefoged, 1996), the dorsal lateral geniculate nucleus (Satorre et al, 1985), and the neostriatum (Sturrock, 1980). In contrast, other studies were unable to detect significant changes in astrocyte number in cerebral cortex (Hansen et al, 1987; Peters et al, 1991; Peters et al, 1994) and the hippocampus (Landfield et al, 1977; Geinisman et al, 1978; Landfield et al, 1978).…”
Section: Discussionmentioning
confidence: 99%